A Critical Study on the Persian Translation of Routledge History of Philosophy - Majid Sadrmajles (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the present paper, we first briefly introduce the book Routledge History of Philosophy: From the Beginning to Plato. Its Persian translation was written by Hasan Mortazawi and published in Iran in 1390(2011)by Philosophy Cheshme Press. After the introductory matters, the present paper focuses on two aspects: the formal aspect of printed translation and 2- the content of Persian translation. Of course this study of the Persian translation is based on the original English text and a comparison between them.On the formal aspect, I consider factors such as title, order and completion, or deficiency of translation.  At the content level of the Persian translation in comparison with the original text, I consider factors as printing errors, names’ spelling in Persian, fluency, and validity of the translation text. The result of this study demonstrates that the Persian translation of the first volume of Routledge History of Philosophy: From the Beginning to Plato is subjected to some unwanted deficiencies. Some other pitfalls include 1- Sometimes the Persian spelling of the special names especially Greek names is not exact or correct. 2- Some of the philosophical terms are not translated in uniformity. 3- The text of Persian translation is not edited by an editor that is expected to be a specialist in the ancient Greek philosophy4- Translator’s nonsufficient acquaintance with the Greek philosophy. Translation of philosophical works as other subjects in theoretical disciplines is a technical work and in addition to the skills of writing and grammar, the editor needs to have special information of the subject matter.  It is hoped that the recommendations of this paper help Mr. H. Mortazawi in revising his translation in the second edition.